Elites and right-wing groups opposing the government of Pedro Castillo in Peru - Goldstein, Ariel (2022)
This paper aims at analyzing the different actors in the Peruvian elites and right-wing groups that make up the opposition to the government of Pedro Castillo. To this effect, a distinction between right-wing groups is made: corporate and finance, media, political and social. A proposition is offered after a careful examination, based on interviews to different actors, and a survey of traditional media and social media. Prior to the arrival of Castillo, the Peruvian right was defined as a “conservative archipelago”. As a response to the crisis it signifies to the Fujimori’s social economic model, the triumph of Castillo and him becoming president seems to have activated a unified block that represents the current embodiment of the Peruvian right. Additionally, the influence of international actors in local politics is also taken in consideration, such as Vox from Spain and the Republican Party from the United States.